Bureaucracy, Pedagogy, Surgery: Keats, Guy's, and the 'Institution' of Medicine. Issue 2 (July 2016) - Robert Allard, James
Abstract : John Keats's time as a medical student provided much fodder for the imagination of readers of all persuasions. In particular, 'Z', in the fourth installment of the 'Cockney School' essays, took pains to ensure that readers knew of his time training to be an apothecary, working to frame Keats, first, as connected to the lowest branch of medical practice, and, second, as having failed as badly at that unworthy pursuit as he did at poetry. But what would 'Z', or any of his readers, have known about the training of an apothecary, about medical pedagogy, about the internal workings of the profession? As outsiders, what could they have known, beyond perception, conjecture, and opinion? And on what were those opinions based? This essay reads 'Z''s comments in the context of first-hand accounts of the state of contemporary medical pedagogy, seeking to account both for 'Z''s dismissal of Keats to 'the shops' and for the continuing fascination with his connections to medicine in these terms.